Embedding play-based learning into junior primary (Year 1 and 2) Curriculum in WA - Jay, Jennifer; Knaus, M. (Social Science Press, 2018)
Governments and their policy decisions inevitably influence the pedagogical practices of teachers. There have been considerable curriculum changes and national reforms in Australia with the implementation of two very different national curricula documents in the early childhood sector in the last decade. The political landscape in Western Australia is even more complex with the mandating of the National Quality Standard (NQS) in all public schools from Kindergarten to Year two. The introduction of the NQS has impacted on the teaching and learning in the early years of school, and in particular, the inclusion of play-based teaching strategies. The tensions that arise from the juxtaposition of these mandated documents is significant to teachers in Years 1 and 2 who in past years have been used to a more didactic and structured approach to early learning. The researchers in this study have sought to explore relevant and current issues impacting on junior primary teachers' pedagogy and practice in relation to the use of play to engage children in learning. Using qualitative methodology, a case study design was chosen and included semi-formal interviews as well as data collected at teacher collaborative meetings. The research identified the necessary supports required for implementing play in the early years of school as well as the challenges experienced by the teachers.